The examination of social capital in hungarian rural communities: the case of Bátya village - Kassai, Zsuzsanna (Studia Mundi – Economica, 2018)
The term ‘social capital’ was first used in the international literature in the beginning of the 20th century by Lyda Judson Hanifan, but it became widely known only in the 1990s and there is still no consensus on how to measure it. In the beginning of the paper a short review can be found concerning the different approaches, definitions and functions of social capital. Then an example for measuring method is presented through a Hungarian case study. In this part, some fundamental social characteristics of the population of Bátya village are examined.
Keywords: social capital; cooperation; general trust; strategic trust; sustainable development